Association of Nutritional Status, Activity Behavior, and Dietary Behavior with Musculoskeletal Complaints in Undergraduate Students - Romadhiyana Kisno Saputri; Putri Rahmasari; Asrina Habiba; Silfi Afifah Al Kibri (Universitas Negeri Surabaya, 2026)
Background: Musculoskeletal complaints are widespread among undergraduate students and are influenced by a number of modifiable lifestyle factors. While it has been shown that physical activity and sedentary behavior influence musculoskeletal health, the joint impacts of nutritional status and dietary behavior are not well established.Objectives: The purpose of this study was to determine the association between nutritional status, exercise behavior, dietary behavior and musculoskeletal complaints in undergraduate students.Methods: This quantitative cross-sectional study was performed on 80 undergraduate students recruited by using purposive sampling. Body weight and height were assessed and BMI was calculated. Activity behavior (physical activity level and sitting duration), dietary behavior, healthy food choices and musculoskeletal complaints were assessed by validated questionnaires. Data were examined using descriptive statistics and Spearman’s rank correlation with p < 0.05 as a level of significance.Results: A majority of participants reported normal nutritional status (76.3%), low physical activity (52.5%), moderate sitting duration (51.3%), bad eating behavior (58.8%), and good healthy food choices (48.8%). Physical activity was adversely correlated with musculoskeletal complaints (r s = −0.560, p < 0.001) while sitting duration was positively correlated (r s = 0.440, p < 0.001). Gender, nutritional status, dietary behavior, and selection of healthy food were not significantly associated with musculoskeletal problems (p > 0.05).Conclusion: Musculoskeletal complaints among undergraduate students are strongly associated with physical activity levels and sitting duration. Encouraging regular physical activity and minimizing prolonged sitting could enhance musculoskeletal health within this population.